Stakeholders’ perspectives to intimate partner violence among married couples in ondo city, Nigeria (2023)
Intimate partner violence (IPV) is conceptualized as interactional events, relationship patterns, undue influences, processes, and behaviour known to both partners involved but largely ignored until blown out of proportion and capable of degenerating into large-scale harm and sometimes death. The study focused on providing a holistic review of the prevalence, precipitating drivers, effects, and plausible solutions to IPV in Ondo City (Ondo West and East Local Government Areas). The study employed a descriptive survey design, which was found appropriate for the study. The participants of the study comprised all adults (18 years and above) who are legally married. The purposive sampling technique was used to select the participants based a sole criterion of being in a marital relationship for over five years. A total of 400 participants were selected from the two local government areas in Ondo City, Ondo State. A validated self-designed instrument titled Questionnaire on Intimate Partner Violence (r= 0.89) with four sub-scales was used to collect data. The collected data were analyzed through SPSS version 22. The finding revealed that the average prevalence was average. Other results revealed the top three precipitating drivers or causes of IPV (extra-marital affairs, financial/economic stress, emotional dependence, & insecurity); effects (injury, wounds, strains, and dislocation, partner continuous disrespect and continuous marital turbulence); and probable solutions (orientation on the marital relationship or journey; sharing and doing things together; deliverance or prayers for the partner) to IPV among married and unmarried couples. It is recommended that there need for community-wide campaign and approaches against IPV; also, avoidance strategies such as alternative dispute resolution system; guidance and counselling mechanisms; remedial course prior marriage.